2008
DOI: 10.31899/rh4.1208
|View full text |Cite
|
Sign up to set email alerts
|

Improving communication between parents and adolescents on reproductive health and HIV/AIDS

Abstract: This study was made possible by the generous support of the American people through the United States Agency for International Development (USAID) under the terms of Cooperative Agreement No. HRN-A-00-98-00012-00. The contents are the responsibility of the FRONTIERS Program and do not necessarily reflect the views of USAID or the United States Government. parents/guardians. The activities were conducted for four months (September 2005-December 2006). Implementation of the intervention was followed by qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Although previous studies have shown that the risk of unintended pregnancy is higher among unmarried women [21,25], this study demonstrates that married women also experience unintended pregnancies. This result is indicative of unmet needs for family planning among urban women in union and the need to pay greater attention to groups traditionally thought to have lower need for family planning.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Although previous studies have shown that the risk of unintended pregnancy is higher among unmarried women [21,25], this study demonstrates that married women also experience unintended pregnancies. This result is indicative of unmet needs for family planning among urban women in union and the need to pay greater attention to groups traditionally thought to have lower need for family planning.…”
Section: Discussioncontrasting
confidence: 70%
“…In Senegal, a recent study demonstrated that about a third of female urban youth ages 15–24 reported being sexually experienced and among sexually experienced female youth, a third had premarital first sex; these youth are at risk of an unplanned pregnancy [ 23 , 24 ]. Other recent studies on youth in Senegal indicate that unintended pregnancies are often the consequence of a lack of knowledge about reproductive and sexual health as well as a lack of communication between young people and their parents [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, low levels of parent–child communication on sexual issues may be explained by the sharing of child-rearing responsibilities between the parents and other family members from the nuclear or the extended family unit [2,5,49]. Third, the formal nature of parent–child relationship is thought to be a factor that restrains the ease of discussion on sexual issues [2,50]. Regardless of these facts, more investigation is needed to determine aspects of parent–child communication such as the timing, the content, the openness or the frequency of communication which could be influential in young people sexual risk-taking in sub-Saharan African settings.…”
Section: Discussionmentioning
confidence: 99%
“…This project was undertaken by the Population Council with CEDPA India as partner to assess the extent to which an intervention focused on developing parenting skills, in general, and on enabling parents to overcome obstacles in communicating with their adolescent children about SRH matters, in particular, succeeded in breaking down hierarchical relations between parents and children and enhancing parent-child communication about physical maturation and SRH matters. The intervention was developed on curriculums that were used in two projects-Improving the communication between parents and adolescent in reproductive health and HIV/AIDS project, implemented by CEDPA and the Population Council in Senegal (Diop and Diagne, 2008), and Better Life Options programme, intended to empower adolescents, transform gender norms and encourage child-parent communication from adolescents' perspective, implemented by CEDPA (CEDPA, 2000); these were modified to reflect the Indian context and the parental perspective, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hence a first step was to develop an appropriate curriculum. CEDPA India, in partnership with the Population Council, reviewed available curriculums and opted to adapt syllabuses from two programmes: one implemented among parents in Senegal (Improving the communication between parents and adolescent in reproductive health and HIV/ AIDS) implemented by CEDPA and the Population Council (the intervention programme focused on parents and on HIV vulnerability) (Diop and Diagne, 2008); and a second implemented among adolescent girls in India (the Better Life Options programme) intended to empower adolescents, transform gender norms and encourage child-parent communication (CEDPA, 2000). CEDPA India synthesised the key lessons from each of these syllabuses, adapted them for implementation among parents, and created a curriculum comprising a total of 16 sessions for mothers, 16 sessions for fathers, and 4 sessions in which adolescent children of participants were also invited to attend.…”
Section: Designing the Curriculummentioning
confidence: 99%